MOTIVATION, WORKLOAD, AND WORK ENVIRONMENT AS DETERMINANTS OF EMPLOYEE PERFORMANCE: INSIGHTS FROM PT MAJU MAKMUR, INDONESIA - Sutoro, Moh.; Solihin, Dede (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study investigates the influence of motivation, workload, and work environment on employee performance at PT Maju Makmur, Indonesia. The research aims to analyze how these factors contribute to improving employee performance within the organization. A quantitative method was employed using the Partial Least Squares (PLS) approach to examine the structural relationships among variables. Data were collected from 120 employees through a structured questionnaire and analyzed using SmartPLS 4. The results reveal that motivation and work environment have a positive and significant effect on employee performance, while workload shows a weaker and insignificant influence. These findings indicate that employees with high motivation and supportive work environments tend to perform better, whereas excessive workload can reduce effectiveness. Therefore, organizations should focus on enhancing motivation and maintaining a conducive work environment while ensuring workload remains manageable to sustain optimal employee performance.